2021
DOI: 10.1038/s41392-021-00724-y
|View full text |Cite
|
Sign up to set email alerts
|

Retro-enantio isomer of angiopep-2 assists nanoprobes across the blood-brain barrier for targeted magnetic resonance/fluorescence imaging of glioblastoma

Abstract: Glioblastoma (GBM), one of the most common primary intracranial malignant tumours, is very difficult to be completely excised by surgery due to its irregular shape. Here, we use an MRI/NIR fluorescence dual-modal imaging nanoprobe that includes superparamagnetic iron oxide nanoparticles (SPIONs) modified with indocyanine (Cy7) molecules and peptides (ANG or DANG) to locate malignant gliomas and guide accurate excision. Both peptides/Cy7-SPIONs probes displayed excellent tumour-homing properties and barrier pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…207,208 Vascular endothelin-2 (Angiopep-2, ANG) peptide from the aprotinin Kunitz domain can specifically target brain cells and bind to low-density lipoprotein receptor-associated protein-1 (LRP1) to achieve targeted delivery, which is overexpressed in the BBB and glioma. [209][210][211] IRGD (CRGD-KGPDC) binds to αvβ3 integrin, which is encapsulated by neuropilin 1 (NRP 1) after its cleavage, and then enters tumour cells through endocytosis. Due to the specificity of these two receptors, iRGD can target multiple tumour cells.…”
Section: Tumour-homing Cppsmentioning
confidence: 99%
“…207,208 Vascular endothelin-2 (Angiopep-2, ANG) peptide from the aprotinin Kunitz domain can specifically target brain cells and bind to low-density lipoprotein receptor-associated protein-1 (LRP1) to achieve targeted delivery, which is overexpressed in the BBB and glioma. [209][210][211] IRGD (CRGD-KGPDC) binds to αvβ3 integrin, which is encapsulated by neuropilin 1 (NRP 1) after its cleavage, and then enters tumour cells through endocytosis. Due to the specificity of these two receptors, iRGD can target multiple tumour cells.…”
Section: Tumour-homing Cppsmentioning
confidence: 99%
“…More often than not, diagnosis is delayed, which further impedes the success of the treatment administered [140]. Furthermore, accurate tumor imaging is of immense importance in the pre-operative stage and the location of tumor margins [141]. In this regard, Angiopep-2-modified nanosystems have demonstrated great potential.…”
Section: Diagnostic and Theranostic Applicationsmentioning
confidence: 99%
“…Xie and coworkers [141] constructed a MRI/NIR fluorescence dual-modal imaging nanoprobe by combining superparamagnetic iron oxide NPs (SPIONs) with the fluorescent dye indocyanine. This was further modified with the retro-enantiomer of Angiopep-2 to prevent its degradation by enzymes of the blood and cells.…”
Section: Diagnostic and Theranostic Applicationsmentioning
confidence: 99%
“…Nonaka et al reported that IF7, an annexin A1-binding peptide, could overcome BBB and deliver chemotherapeutics to target brain tumors ( Nonaka et al, 2020 ). Xie and coworkers demonstrated that d-peptide ligand of angiopep-2 modified nanoprobes could cross BBB and locate glioma sites ( Xie et al, 2021 ). Lim and collaborators found that dNP2 peptide could penetrate BBB and deliver ctCTLA-4 protein to ameliorate autoimmune encephalomyelitis in mouse models ( Lim et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%